Literasi Digital dan Berkembangnya Hate Speech di Media Sosial dalam Pilpres 2024 - Lenda Tri Hardianti (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
In the 2024 presidential election, political activity on social media is very intensive, with the aim of attracting people's attention and voting power towards presidential candidates. However, the low literacy level of Indonesian society often triggers negative behavior such as hate speech. This research aims to describe the behavior of hate speech on social media towards the 2024 Presidential candidate of the Republic of Indonesia. The method used in this research is a qualitative approach. The research results show that there are still many individuals who use social media to express their dislike of presidential candidates in negative ways, including through hate speech. Many social media users are unaware of the legal implications of their actions. This situation requires public vigilance and wisdom in using social media to avoid negative things. To overcome this problem, digital literacy is not enough to just focus on models such as critical consuming, functional prosuming, and critical prosuming. This research suggests adding a moral values ​​model that includes two main indicators: ethical behavior and motivation skills. Hate speech can appear either in the form of hoaxes or true information, so a moral value-based approach is very necessary to increase people's awareness and responsibility in interacting in cyberspace. This research emphasizes the importance of more comprehensive digital literacy education to combat the spread of hate speech on social media during the 2024 presidential election.